2021
DOI: 10.1038/s41588-021-00838-7
|View full text |Cite
|
Sign up to set email alerts
|

Chromothripsis as an on-target consequence of CRISPR–Cas9 genome editing

Abstract: Genome editing has promising therapeutic potential for genetic diseases and cancer (1, 2). However, the most practicable current approaches rely on the generation of DNA double-strand breaks (DSBs), which can give rise to a poorly characterized spectrum of structural chromosomal abnormalities. Here, we show that a catastrophic mutational process called chromothripsis is a previously unappreciated consequence of CRISPR-Cas9-mediated DSBs. Chromothripsis is extensive chromosome rearrangement restricted to one or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
254
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 360 publications
(301 citation statements)
references
References 89 publications
7
254
0
Order By: Relevance
“…1B). 15 In the paper, the authors observed high overall editing efficiency and a significant increase in micronucleus formation compared to cells transfected without guide RNA. Micronucleation frequency ranged between 4% and 7.5% of edited cells.…”
Section: Crispr and Chromothripsis: Proceed With Cautionmentioning
confidence: 95%
See 4 more Smart Citations
“…1B). 15 In the paper, the authors observed high overall editing efficiency and a significant increase in micronucleus formation compared to cells transfected without guide RNA. Micronucleation frequency ranged between 4% and 7.5% of edited cells.…”
Section: Crispr and Chromothripsis: Proceed With Cautionmentioning
confidence: 95%
“…Writing in Nature Genetics, Leibowitz et al put large genomic rearrangements under the microscope once more, revealing a diversity of genomic alterations that have not previously been appreciated. 15 Importantly, the authors identify evidence for chromothripsis-a process where a single catastrophic event shatters the genome, and the resulting reassembly leads to mass genomic reorganization (Fig. 1A).…”
Section: Crispr and Chromothripsis: Proceed With Cautionmentioning
confidence: 99%
See 3 more Smart Citations